Annual World Bank Conference on Development Economics, 2005 : lessons of experience - Bourguignon, François; Pleskovic, Boris (World Bank Latin American and Caribbean studies. Proceedings., 2005)
"This year's volume, Annual World Bank Conference on Development Economics 2005, presents selected papers from the 16th ABCDE meetings, held in May 2004. It reviews the lessons of 60 years of development experience, addressing key topics such as infrastructure, behavioral economics, trade, poverty, and globalization."